Pengaruh Pemberian Jenis Amelioran Terhadap Pertumbuhan Dan Produksi Bayam (Amaranthus tricolor L.) Pada Tanah Gambut: The Efect of Ameliorant on the Growth and the Harvest of Spinach (Amaranthus tricolor L.) on the Peat Land - Sari, Yunita Purnama; Haryadi, Haryadi; Arfianto, Fahruddin (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2020)
The lowness of productivity of spinach in Central Kalimantan is related to the kind of land used in the cultivation of the crop. This research attempt to find the effect of ameliorant on the growth and the harvest of spinach. The research was conducted from December 2018 until February 2019 in Kebun Percobaan dan Penelitian (KP2) Universitas Muhammadiyah Palangkaraya, Jln. Anggrek, Kelurahan Kereng Bengkirai, Kecamatan Sebangau, Kota Palangkaraya, Provinsi Kalimantan Tengah. The ameliorant applied in the research were chicken manure, dolomite and limestone. The research was conducted in the completely random design with five replications. The results indicate that the ameliorant significantly affected the plant height and the number of leaves on the 14, 21 and 28 day after plantation. The ameliorant also affected on the plant fresh weight significantly.